Correlation Between Body Mass Index, Waist Circumference, and Body Fat with Oxidative Stress in Obese Adolescents - Estuti, Wiwit; Kunaepah, Uun; Nurcahyani, Lia (Window of Health : Jurnal Kesehatan, 2023)
Teenagers are one of the age groups that are prone to obesity. Obesity experienced by adolescents is a nutritional problem that is increasing rapidly and has become a significant public health problem. Obesity occurs due to an imbalance in energy intake over time, resulting in excessive fat accumulation and weight gain. This study aimed to identify the relationship between body mass index (BMI), waist circumference, and percent body fat with markers of oxidative stress in obese adolescents. The research method is an experimental research. The subjects of the study were 24 adolescents aged 13-15 years. Data were collected using a questionnaire and analysis of malondialdehyde (MDA) and superoxide dismutase (SOD) levels in the subject's blood serum. In addition, data in the form of BMI, percent body fat, waist circumference, pattern, and level of food consumption. Data analysis was carried out descriptively and inferentially at the significance level to determine the differences in treatment using the t-test if the data were normally distributed and the Mann-Whitney test if the data were not normally distributed. The closeness of the relationship was found using the Pearson correlation test. The results showed a moderately significant negative correlation between percent body fat and serum MDA, but body mass index and waist circumference were not significant. The higher the percentage of body fat, the lower the serum MDl. There is no significant relationship between BMI, LP, and % LT with serum SOD.